(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Symptoms vary depending on the type and stage of the disease, but common symptoms include a sharp aching pain in the affected area, pain when chewing food or pressing on the tooth, and a feeling that the tooth is cracking from the inside. Patients often have pus discharge from the gums and an unpleasant odor from the oral cavity. The gums become red, swelling of soft tissues appears. Sometimes the pain spreads to the ears or temples.